The Fifth Order of Design - Mariana Fonseca Braga (Cubic Journal)
Failures in achieving sustainability are being recognised worldwide. Approaches to tackling sustainability challenges often fail to address the roots of these challenges. This paper contributes to a necessary discussion of an emerging necessity, a research agenda that encompasses the transformative strategic role and value of design in (co-)shaping sustainable and equitable futures. It draws attention to drivers of unsustainability and their complex interplay of design, environmental, economic, societal and individual values that govern our modern society. Richard Buchanan’s four orders of design model is reviewed in the process, with a fifth order being suggested to deal with the change of paradigm that sustainability requires. This comprehensive view is critical to tgetting to grips with global challenges (United Nations Sustainable Development Goals) since the shift towards sustainability needs to address the root causes of systemic and interrelated problems that cannot be overcome by reactive marketing and technocratic approaches. Implications for design value, education, skills, and ways of designing are pointed out.